'A new and disturbing form of subversion': Militant Tendency, MI5 and the threat of Trotskyism in Britain, 1937-1987. Issue 3 (3rd July 2022) - Kassimeris, George; Price, Oliver
ABSTRACT: This article examines how the rise of Militant Tendency transformed MI5's perception of Trotskyism's ability to pose a threat to the British state. Militant's emergence in the 1970s as an entryist organisation within the Labour Party and its subsequent influence on Liverpool City Council in the early 1980s led security officials to consider it as an equal if not greater subversive threat than the Communist Party of Great Britain (CPGB). Drawing on newly released files, the article adds to the understanding of counter-subversive investigations in Cold War Britain and assesses how, between the late 1970s and early 1980s, Militant became the first and, so far, only Trotskyist group to be considered by MI5 a significant subversive threat to British internal security.